2008
DOI: 10.1101/gr.073601.107
|View full text |Cite
|
Sign up to set email alerts
|

Direct targets of the TRP63 transcription factor revealed by a combination of gene expression profiling and reverse engineering

Abstract: Genome-wide identification of bona-fide targets of transcription factors in mammalian cells is still a challenge. We present a novel integrated computational and experimental approach to identify direct targets of a transcription factor. This consists of measuring time-course (dynamic) gene expression profiles upon perturbation of the transcription factor under study, and in applying a novel "reverse-engineering" algorithm (TSNI) to rank genes according to their probability of being direct targets. Using prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…Knockdown or knockout of p63 in epithelial cells to identify de-regulated genes [14, 17] has been the major approach in previous p63 target gene studies. The main drawback of this approach is that loss of p63 results in epithelial differentiation defects, and genes that are expressed at a later stage of differentiation and regulated by p63 may not be identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Knockdown or knockout of p63 in epithelial cells to identify de-regulated genes [14, 17] has been the major approach in previous p63 target gene studies. The main drawback of this approach is that loss of p63 results in epithelial differentiation defects, and genes that are expressed at a later stage of differentiation and regulated by p63 may not be identified.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have aimed at the identification of p63 target genes to understand the role of p63 in epidermal differentiation. Some studies took the RNAi approach to knock down p63 in proliferating keratinocytes and identified several hundreds of potentially p63-regulated genes [14, 17]. However, as p63 -depleted keratinocytes have differentiation defects [14, 17], potential direct p63 target genes at later stages of epidermal differentiation might not be identified using this approach.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ARACNe [3] focuses on the targets prediction using mutual information measures. Ordinary Differential Equations (ODEs) and controlled perturbation are used in TSNI [4]. Bayesian network and Dynamic Bayesian network inference are employed in Banjo [5].…”
Section: Introductionmentioning
confidence: 99%